What is proton pump inhibitors unresponsiveness in gastroesophageal reflux disease? How should these cases be managed? - Çelebi, Altay; Yılmaz, Hasan (Turkish Journal of Gastroenterology, 2017)
Abstract Proton pump inhibitors become the most potent therapeutic option in gastroesophageal reflux disease. Unresponsiveness to this treatment is not uncommon in clinical practice. We reviewed the definition of PPI unresponsiveness and the management of this situation. Cite this article as: Çelebi A, Yılmaz H. What is proton pump inhibitors unresponsiveness in gastroesophageal reflux disease? How should these cases be managed? Turk J Gastroenterol 2017;28(Suppl 1); S71-S72 Full Text Turkish